الإشكالات التطبیقیة في المصارف الوقفیة من منظور الفقھ الإسلامي - Alaa Adel Alobaid; Younes Soalhi (Al-Ahkam, 2015)
Waqf is considered to be one of the most important institutions of voluntary sector which exists in the Islamic heritage. Waqf have a dual function; religious and social, which makes it still always exist until today. In performing its role, waqf institutions will face the problems of the management of waqf. Blurring property ownership of institutions of social charity with waqf property, is one of the problems experienced by those waqf institutions. Besides that what needs to be done if the results of the management of waqf property is still lacking to fulfill the rights of mawqūf ‘alayh or oppositely. The other problem is about the right of mawqūf ‘alayh to rent waqf property below the standard prices. This paper aims to describe the problems mentioned above as well as effort to solve the problems in authoritative Islamic perspectives. One of the methode is the implementation of tarjīḥ to the scholars argumentations.